Costeffectiveness in mathematical modelling of the power unit control - Popov, Oleksandr; Shmatko, Nataliia; Budanov, Pavlo; Pantielieieva, Iryna; Brovko, Kostiantyn (Eastern-European Journal of Enterprise Technologies, 2019)
The authors of the study have analysed the criteria for increasing cost-effectiveness in the operation of power-generating equipment of power units at TPPs and NPPs. The existing methods of calculating the cost-effectiveness disregard factors that lead to economic costs during shutdowns of the power unit and reduce the energy consumer load. A significant factor in increasing cost-effectiveness of the automated control systems at a power unit of a power plant is the compulsory checking to detect a low level of information reliability. It is proved that reliability of the power unit technological equipment substantially depends on the effectiveness of emergency automated control when an unpermitted shutdown of a power unit occurs due to false positives. It is shown that the cause of false positives is low reliability of the data on the power unit technological process parameters. It is revealed that unforeseen unpermitted shutdown of a power unit and a decrease in the energy consumer load leads to significant economic and material losses, and, consequently, to a decrease in economic efficiency of automated control of a power unit. It is shown that the existing economic models do not take into account the financial and material costs that occur due to unpermitted shutdown of the power unit and decrease in the energy consumer load in case of false positives in real time. The authors of the study have devised a unified integrated economic and mathematical model, which allows calculating the economic effect taking into account changes in the reliability of the technological equipment, due to the timely prompt detection of false positives and low-reliability data. The proposed emergency modular unit coupled with modules for detecting and control of false alarms, which takes into account static and operational economic components, allows calculating the economic effect based on the devised unified integrated economic and mathematical model. The authors of the study give practical recommendations for applying the economic module in the hardware and software complex of the power unit, which allows calculating the economic effect on the basis of static data coming from the data memory and current data from the power unit